Guidelines for food system profile development at sub-national levels in Vietnam - Pham Thi, Huong Mai; Huynh Thi, Tuyen Thanh; Nguyen, Quoc Minh; Viet Anh, Bui Thi; Bene, Chris; Lundy, Mark (2025)
The guidelines support interdisciplinary/intersectoral groups and local and provincial authorities in co-developing food system profiles that highlight key aspects of the local food system, such as notable features, trends, accomplishments, and challenges of each food system element. Profile development is a key activity that supports the implementation of the National Action Plan on Food Systems Transformation towards Transparency, Responsibility, and Sustainability by 2030 (NAP-FST) at sub-national levels.